Pericardial disease in patients treated with immune checkpoint inhibitors. Issue 6 (18th June 2021) - Gong, Jingyi; Drobni, Zsofia Dora; Zafar, Amna; Quinaglia, Thiago; Hartmann, Sarah; Gilman, Hannah K; Raghu, Vineet K; Gongora, Carlos; Sise, Meghan E; Alvi, Raza M; Zubiri, Leyre; Nohria, Anju; et al.
Abstract : Background: There are limited data on the occurrence, associations and outcomes of pericardial effusions and pericarditis on or after treatment with immune checkpoint inhibitors (ICIs). Methods: This was a retrospective study at a single academic center that compared 2842 consecutive patients who received ICIs with 2699 age- and cancer-type matched patients with metastatic disease who did not receive ICI. A pericardial event was defined as a composite outcome of pericarditis and new or worsening moderate or large pericardial effusion. The endpoints were obtained through chart review and were blindly adjudicated. To identify risk factors associated with a pericardial event, we compared patients who developed an event on an ICI with patients treated with an ICI who did not develop a pericardial event. Cox proportional-hazard model and logistical regression analysis were performed to study the association between ICI use and pericardial disease as well as pericardial disease and mortality. An additional 6-week landmark analysis was performed to account for lead-time bias. Results: There were 42 pericardial events in the patients treated with ICI (n=2842) over 193 days (IQR: 64–411), yielding an incidence rate of 1.57 events per 100 person-years. There was a more than fourfold increase in risk of pericarditis or a pericardial effusion among patients on an ICI compared with controls not treated with ICI after adjusting for potential confounders (HR 4.37, 95% CI 2.09 to 9.14, p<0.001). Patients who developed pericardial disease while on an ICI had a trend for increased all-cause mortality compared with patients who did not develop a pericardial event (HR 1.53, 95% CI 0.99 to 2.36, p=0.05). When comparing those who developed pericardial disease after ICI treatment with those who did not, a higher dose of corticosteroid pre-ICI (>0.7 mg/kg prednisone) was associated with increased risk of pericardial disease (HR 2.56, 95% CI 1.00 to 6.57, p=0.049). Conclusions: ICI use was associated with an increased risk of development of pericardial disease among patients with cancer and a pericardial event on an ICI was associated with a trend towards increase in mortality.